10.61533 KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN PADA PENDAPATAN ASLI DAERAH KOTA PANGKALPINANG DALAM UPAYA IMPLEMENTASI PEMBANGUNAN EKONOMI BERKELANJUTAN (Studi di Kelurahan Jerambah Gantung) - Khairun Nisak; Hendarti Tri Setyo Mulyani; Deara Shinta Lestari (STIE IBEK Pangkalpinang, 2025)
The aim of this research is to determine the contribution of PBB P2 (Land and Building Tax) to the Regional Original Income of Pangkalpinang City in efforts to implement sustainable economic development. This research uses a qualitative approach. The data was collected through unstructured interviews with 5 respondents, consisting of the Village Head, Head of Development, and RT (Neighborhood Association) Chairman in Jerambah Gantung Village. The data analysis used Data Collection, Data Conclusion, Data Display, and Conclusion Drawing/Verification. The data analysis results show that the contribution of PBB P2 in Jerambah Gantung Village is 41.39% of the target of 321 million, which affects the Regional Original Income of Pangkalpinang City, exceeding the target by 101.96%, with a target of 122.2 billion. This income is then allocated to the Regional Budget (APBD), which is used for development in Pangkalpinang City.